DETERMINATION OF ORGANOCHLORINATED PESTICIDE AND POLYCHLORINATED BIPHENYL CONGENERS RESIDUES IN CHICKEN EGGS BY GAS CHROMATOGRAPHY - (:unkn) unknown (My University, 2018)
The aim of this study was to determine the concentrations of organochlorinated pesticides (OCPs) and polychlorinated biphenyls (PCBs) congeners in chicken eggs obtained from various locations in Turkey by gas chromatography and valitadion of the results using differentdetector systems (MS, MS/MS and ECD). In total, eighteen OCP and PCB compounds were analysed in hundred egg samples. Only b-HCH, 4,4-DDE and PCB138 were found in nine eggsamples at concentrations of 5.1-7.2 µg/kg, 8.4-30 µg/kg and 4.2 µg/kg respectively. The detected concentrations of these compounds were found to be lower than the maximum residue levels (MRLs) set by EU. The recoveries, relative standard deviations (RSD), limit of detection (LOD) and limit of quantification (LOQ) were found in the range of 83-111%, 0.9-14.1%, 1.2-3.5 µg/kg and 0.3-10.0 µg/kg respectively.
Keywords: Gıda Bilimi ve Teknolojisi